Menafsir Baby Grave di Kalimbuang Bori’ Toraja: Memahami Ruang, Budaya dan Perubahan di Era Modernitas - Hasrin, Sri Wahyuni; Muhammad, Zakiyudaulah; Alwiyah, Tri Nur; Kurniawan, L. M. Rezky; Sanda, Sanda; Silsiyana, Jusnita; Ridwan, Serly Novita; Fatwa, Fatwa; Salsabila, Kalsum Azizah; Allobunga', Immanuel (DISCOURSE: Indonesian Journal of Social Studies and Education, 2025)
The infant burial tradition in Kalimbuang Bori’, Toraja, is an integral part of the local culture that is rich in symbolism, reflecting the community's beliefs about the cycle of life and death. This study aims to answer three main questions: first, the meaning and role of baby graves in the formation of social and spiritual values of the Kalimbuang Bori' community; second, the location selection and spatial interaction of the baby grave tradition with the natural environment that influences the community's culture; and third, the role of the younger generation of Toraja in preserving this tradition amidst the influence of modernization. Primary data collection methods were carried out through interviews, questionnaires, documentation, and direct observation in the field, while secondary data were obtained from scientific journal articles, map databases, and other research papers. The analysis method used is descriptive qualitative, which allows researchers to explore the meaning of this tradition in depth. This study adopts the Environmental Determinism Theory to explain how culture is shaped by the natural environment. The results show that the baby grave tradition reflects deep social and spiritual values and shows a close relationship between humans and nature. The role of the younger generation is very important in preserving this tradition so that cultural values remain alive amidst the challenges of modernization, and it is hoped that this research can provide deeper insight into the interaction between space and culture in the context of infant burials in Toraja.